Dalí Sign: Characterization and Case Series of Patellar Bony Shell Morphological Changes after Two-Stage Revision for Periprosthetic Joint Infection - Hohmann, Alexandra L.; DeSimone, Cristian A.; Leipman, Jessica H.; Fillingham, Yale A.; Lonner, Jess H. (The Journal of Knee Surgery, 2025)
The fate of the patella in two-stage revision total knee arthroplasty (TKA) for periprosthetic joint infection (PJI) in which the patella is left as a bony shell is poorly described. The purpose of this case series is to describe a phenomenon we name the Dalí Sign, which is characterized by elongation and curvature of the patella around the lateral edge of the femoral component occasionally observed in patients undergoing two-stage revision without reimplantation of the patellar component. Our institutional surgical database was queried for patients who were treated with two-stage revision arthroplasty for PJI by the two senior authors. All available sequential skyline patellar radiographs were viewed from immediately prior to first-stage explantation to latest image at final outpatient follow-up at our institution and assessed for the abovementioned morphological changes. Included patients underwent a two-stage revision surgery for PJI at our institution, had a patellar component removed during the first stage of their treatment which included implant explantation and insertion of temporary antibiotic spacers, did not have the patellar component reimplanted during their second-stage revision surgery, and demonstrated radiographic patellar morphological changes at final follow-up. Patients' demographic, surgical, and outcome data were recorded. Our review identified six patients meeting these criteria. Mean follow-up after second-stage surgery was 12 months (range 2 to 21 months). At final follow-up, three patients were walking without pain, one patient was exercising to tolerance, one patient was walking with pain, and one was using a wheelchair or a walker for mobility. In this case series, we characterize the Dalí Sign, the elongation and curvature of the patellar bony shell over the femoral component after two-stage revision for PJI. Further comparative cohort studies are necessary to identify the incidence and risk factors for the development of this morphological change and to compare outcomes of patients with and without the Dalí Sign when left with a bony shell after staged revision TKA.
Keywords: patella resurfacing; total knee arthroplasty; TKA; PJI; periprosthetic joint infection